Homeless population, volunteering during pandemic: experience report (Research, Society and Development, 2021)
To identify, through an experience report, the health demands of the homeless population, and report how care is provided by this population, who often do not resort to the SUS out of shame, or fear of being victims of prejudice, highlighting the importance of volunteering in this pandemic period. This is an experience report in a descriptive way, about Collective volunteering Unified by the Homeless Population, the services are carried out at the Former Liceu de Artes e Ofícios, provided by the Catholic University of Pernambuco (UNICAP) in Recife-PE. At the beginning of the pandemic, the intention was to serve as a cleaning point, the space grew in demand and possibilities, there were almost thirty thousand assistances and more than 1500 people registered. There is resistance on the part of the PSRs to go to the UPAs, as there is not always a good reception, and there are also socioeconomic difficulties for moving. Volunteering with the homeless population during the pandemic is an awakening of solidarity and empathy, it is possible to see beauty in the streets amidst the chaos and misery.